2012
DOI: 10.1075/aila.25.04for
|View full text |Cite
|
Sign up to set email alerts
|

Academics’ beliefs about language use and proficiency in Spanish multilingual higher education

Abstract: Today, more and more universities in Spain are starting to design language policies, usually including Spanish and English. At the same time, Spain has a special socio-political context since part of its territory is already bilingual. This paper examines the opinions and attitudes of academics at a bilingual Valencian-Spanish university which is about to implement a multilingual policy adding English as a third language of instruction. Therefore, in order to start planning the implementation of the teacher de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Student 5 said that "Physics is already difficult and English makes it more difficult." Similarly, several studies conducted in different context found that the students in their study reported much language difficulty in the discursive construction of knowledge in English (Fortanet-Gómez, 2012;Ball & Lindsay, 2013;Cots, 2013;Al-Mashikhi, Al-Mahrooqi, & Denman, 2014;Hu & Lei, 2014).…”
Section: Students' Difficultiesmentioning
confidence: 71%
“…Student 5 said that "Physics is already difficult and English makes it more difficult." Similarly, several studies conducted in different context found that the students in their study reported much language difficulty in the discursive construction of knowledge in English (Fortanet-Gómez, 2012;Ball & Lindsay, 2013;Cots, 2013;Al-Mashikhi, Al-Mahrooqi, & Denman, 2014;Hu & Lei, 2014).…”
Section: Students' Difficultiesmentioning
confidence: 71%
“…Naves and Muñoz (2000) highlight the positive contribution of CLIL in the learning of both a foreign language and subject content, as well as the development of the students' solving problem skills. In a similar vein, Mehisto, Marsh, and Frigols (2008) (Dafouz, Núñez, Sancho, & Foran, 2007;Coyle et al, 2010;Aguilar & Rodríguez, 2012;Fortanet-Gómez, 2012;Martín del Pozo, 2015).…”
Section: Literature Reviewmentioning
confidence: 87%
“…Spain has increasingly paid attention to multilingual education in recent years (Breton & Ruiz, 2008;Cenoz, 2008;Fortanet-Gomez, 2012;Gorter & Cenoz, 2017;Moore, 2016;Perez-Milans & Patino-Santos, 2014). In the region of Madrid, the Ministry of Education and the Consejeria de Educacion (Regional Ministry of Education of Madrid) had implemented the bilingual programme in public bilingual schools in 2004.…”
Section: Contextmentioning
confidence: 99%